Leadership, communication, self-esteem, and job performance among employees in Hospital KPJ Sentosa Kuala Lumpur / Aiman Hamzah and Nur Liana Mat Wazir - Hamzah, Aiman; Mat Wazir, Nur Liana (2022)
The purpose of the study was to examine the relationship of leadership, communication, and self-esteem that influence the employee job performance in KPJ Hospital Sentosa Kuala Lumpur. Performance could be defined as an act to achieve a set of goals or goals that have been set that could be a role and organization. This study uses simple random sampling techniques in collecting the data’s survey. This study has adopted instruments from previou study and by using self-administered questionnaires, which the respondents will be among the medical and non-medical personnel in KPJ Hospital Sentosa Kuala Lumpur. The findings indicate that leadership and communication were significantly associated with performance and self-estee were insignificantly associated with performance. Therefore, these studies uniquely position itself to make both theoretical and empirical contributions to the multi-domain literature in the human resources management and psychology literature.